Acid hydrolysis of waxy starches with different granule size for nanocrystal production. (January 2018) - Sanchez de la Concha, Brenda B.; Agama-Acevedo, Edith; Nuñez-Santiago, Maria C.; Bello-Perez, Luis A.; Garcia, Hugo S.; Alvarez-Ramirez, Jose
Abstract: Acid hydrolysis of waxy maize and amaranth starches was achieved for nanocrystal production. Both starches are of the waxy type with an A-type crystallinity pattern. The mean granule sizes were ∼1–2 μm for amaranth starch and ∼15–18 μm for waxy maize. The starches (15 g dry basis) were subjected to acid hydrolysis with 100 mL of 3.16 M H2 SO4 at 40 °C for 3, 5 and 10 days. The hydrolysis extent was higher for amaranth starch, which had a smaller granule size, although the nanocrystal yield was lower because the hydrolysis reactions were more likely to destroy the more crystalline regions. The X-ray diffraction analysis showed that the relative crystallinity increased by approximately 50% after ten days of hydrolysis, although the intrinsic crystallinity order as indicated by the Miller indices was greatly affected. A determination of the chain length distribution showed that a smaller granule size favoured the formation of shorter chains because the hydrolysis reactions were promoted by the relatively small resistance of proton transport to the inner granule region. Highlights: Hydrolysis extent was higher for amaranth than waxy maize starch. Arrangement of starch chains in the crystalline lamella affected hydrolysis extent. Nanocrystals yield was higher in waxy maize than amaranth starch. Difference in chain-length distribution of both nanocrystals was found.